Estudio epidemiológico y rehabilitación de las patologías más frecuentes de los/as jóvenes del centro de protección al discapacitado de Loja (CEPRODIS) durante el periodo marzo – julio del 2010 - Criollo Jimenez, Tania Jaqueline (2010)
The present work executed it to him in CEPRODIS (Centro de Protección al Discapacitado) of the city of Loja, by means of an analytic, descriptive study and of prevalence in 43 youths with different capacities to determine the state of buccal health, in the understood period of March to September of 2010 with the objective of identifying the buccal main illnesses, then to proceed to the rehabilitation of the same ones and this way to improve the opposing state of buccal health. Ages evaluated were 13 to 62 years, of both sexes, which cooperated with the review, the risk factor more frequent was the diet cariogénica and disability that present, because, as knows physical limitations or the intellectual deficiency make oral hygiene is a very difficult situation to address in these patients. The diseases with the highest incidence were dental caries found in 42 patients (97.7 %), periodontal disease in 37 patients (86%), dysfunction of the joint temporomandicular in 33 patients (76.7 %), wear and pigmentations in 32 patients (74.4 %), malocclusion in 30 patients (69.8%) and malposición found in 26 patients (60.5%); with what the necessity was demonstrated of to implement and to execute actions of health that promote the prevention from the home so that next to the Odontologist and General practitioner they allow to give solution to the main problems found in these patients.